Hubungan Genetika Pria Masyarakat Sembiran dan Tri Wangsa di Bali - I Ketut Junitha; Bambang Suryobroto (Fakultas Biologi | Universitas Jenderal Soedirman, 2010)
Balinese community has evolved since the prehistoric era. The present community is structured into Hinduism caste (Brahmana, Kesatria, Wesia and Sudra), but remnants of their ancient communities, collectively called Bali Aga, have not undergone this structure. The first three castes of modern Balinese that comprises Tri Wangsa gentry were derived from JavanesekingdomofMajapahit(1343 AD). One of Bali Aga communities is Sembiran of Northern Bali. Using chromosomal microsatellite DNA, allelic variability of Sembiran and Tri Wangsa communities was reported. Both of them had the same high frequency of alleles which suggested genetic intermixing or sharing of common ancestor. However, a few alleles were unique for each community. This uniqueness was related to patrilineal system of Balinese community and to high mutation rate of Y chromosomal microsatellite DNA.